Spider wasps (Hymenoptera: Pompilidae) of the Dominican Republic - Waichert, Cecilia; Rodriguez, Juanita; Von Dohlen, Carol D.; Pitts, James P. (Zootaxa, 2012)
We recorded 33 species in 19 genera of spider wasps from the Dominican Republic, of which four species are newlydescribed here: Auplopus charlesi Waichert & Pitts, sp. nov., Dipogon (Deuteragenia) marlowei Waichert & Pitts, sp.nov., Notocyphus anacaona Rodriguez & Pitts, sp. nov., and Priocnessus vancei Waichert & Pitts, sp. nov. Eight generaare reported from the Dominican Republic for the first time: Aporinellus Banks, 1912, Caliadurgus Pate, 1946, DipogonFox, 1897, Drepanaporus Bradley, 1944, Epipompilus Kohl, 1884, Notocyphus Smith, 1855, Priocnemis Schiødte, 1837,and Priocnessus Banks, 1925. Nine species are new records for the country: Ageniella (Ageniella) bruesi (Banks, 1928),Ageniella (Ageniella) violaceipes (Cresson, 1865), Aporinellus medianus Banks, 1917, Auplopus bellus (Cresson, 1865),Caliadurgus maestris Alayo, 1969, Drepanaporus antillarum (Bradley, 1944), Drepanaporus collaris (Cresson, 1865),Epipompilus pulcherrimus (Evans, 1955), and Priocnemis cornica (Say, 1836). Pompilus flavopictus Smith, 1862 is ajunior synonym of Poecilopompilus mixtus (Fabricius, 1794), syn. nov. and Odontaporus simulatrix (Bradley, 1944) isjunior synonym of Drepanaporus collaris (Cresson, 1865), syn. nov. New combination is proposed for Aporus (Aporus)antillarum (Bradley, 1944) which is transferred to Drepanaporus. Hitherto unknown males of Ageniella (Ageniella)domingensis (Banks, 1944) and Drepanaporus antillarum (Bradley, 1944) are described and illustrated. Ilustrated keys for subfamilies and species of the Dominican Republic pompilids are provided.Keywords:Pepsinae, Pompilinae, Ctenocerinae, Ceropalinae, key, new record, new species, Caribbean